OPHIOLITES AND GLOBAL GEOCHEMICAL CYCLES: IMPLICATIONS FOR THE ISOTOPIC EVOLUTION OF SEAWATER - Gregory R.T. (My University, 2004)
Isotopic profiles through ophiolite complexes provide the necessary link between the study of global geochemical cycles and plate tectonics. The hydrothermal circulation that occurs beneath the sea floor is the primary mechanism for exchange between the mantle of the Earth and the hydrosphere. The subduction of the hydrothermally altered crust and overlying sediments is the primary mechanism for crustal recycling. Oxygen and strontium isotopes of seawater track the competition between continental weathering and mid-ocean ridge hydrothermal exchange to control the composition of the oceans. Information derived from ophiolite studies on the elemental fluxes and the depth of seawater penetration into the oceanic crust provides constraints on the important rate constants associated with these competing processes. The same tectonic rates that account for the Sr isotope evolution of seawater indicate that the oxygen isotopic composition of the ocean is constrained to vary within narrow limits (per mil level). Isotopic analysis of dredge samples and ophiolite complexes demonstrates that seawater-ocean crust interactions result in a oxygen isotopic zonation of the oceanic crust with masses (concentration times volume) centred on the initial isotopic composition of the crust. This requires that the oxygen isotopic composition of the ocean resides at near steady-state conditions over Earth history. The inferences from ophiolite complexes contrast strongly with the results of measurements on carbonates from epicontinental seaways, particularly for the Palaeozoic. Ophiolites and greenstone belts track exchange processes between the ocean and the igneous crust whereas most carbonate measurements track the surface ocean on continental shelves. For oxygen isotopes, the mass of epicontinental seaways and the rates of meteoric water input suggest a resolution to the controversy that accounts for both data sets.